(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The Human Resource Management System (HRMS) is a system that may structure and comprehensively simplify multiple human resource tasks, empowering individuals to improve their knowledge and abilities for career growth. These will provide a simpler method for moving the organization and its people toward goals while avoiding risk. This project study attempted to eliminate the harm caused to any developing organization by poorly managed employee evaluation, a lack of career pathing, and employee information vulnerability. To address the concerns and problems identified in this project study, the project team created a Human Resource Management System at Bestlink College of the Philippines. As a result, it solves the issues and difficulties that human resource management faces. This results in a more efficient method of assessing employee competency, a discernible improvement in employee retention, a secured career path because of the implementation of Succession Planning, a more central role for learning and development programs in every business, and finally, a Multipurpose Employee’s Profile that is flexible enough to be accessed from mobile and desktop. This project will improve the operation and functionality of the Human Resources Department. The integration of the system in this project will make all of the reports required to assess each employee, including selecting applicants for the specific position, accessible to efficiently analyze employee competency, learning, and training development. Furthermore, a centralized employee profile allows each individual to check personal details such as schedules, pay stubs, and more, including announcements, from a computer or mobile browser.